Data integrity verification for cloud storage - Zhang, Haoran (Nanyang Technological University, 2024)
As Singapore cements its position as one of the world's largest bunkering hubs, the nation's economy increasingly relies on an efficient and transparent marine fuel supply chain.[1] This project aims to develop an advanced digital system for the collection, verification, and storage of bunkering data, ensuring data integrity and security. The system comprises two core parts: software and artificial intelligence (AI).